2021
DOI: 10.35848/1347-4065/ac1250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reduced pressure crystallization on ferroelectric properties in hafnium-zirconium dioxide films deposited by sputtering

Abstract: The impact of reduced pressure annealing on ferroelectric properties in hafnium-zirconium oxide (HZO) films deposited by sputtering has been investigated. It is demonstrated that the HZO films annealed at 600 °C at less than 100 Pa show excellent ferroelectric properties, whereas the HZO films annealed at more than 1000 Pa show degraded electrical properties. This is presumably due to the introduction of oxygen vacancies, which stabilize the ferroelectric orthorhombic phase. Thermal stability can be also impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A summary of previous studies on sputtered HZO ,,,,, and this work is visualized in Figure . Most of the published results show that an annealing temperature higher than 500 °C was required to achieve good FE properties of the sputtered HZO films.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of previous studies on sputtered HZO ,,,,, and this work is visualized in Figure . Most of the published results show that an annealing temperature higher than 500 °C was required to achieve good FE properties of the sputtered HZO films.…”
Section: Resultsmentioning
confidence: 99%
“…We applied the film to fabricate Pt/La-HZO/ITO/Pt metal-ferroelectric-semiconductor (MFS) structures to evaluate the stability of the o-phase because we found that the 8 at% La-HZO films annealed at 800 °C possessed good ferroelectric properties for the MFM structure. [23,24] We deposited a thin ITO layer by performing CSD on the La-HZO layer; it was crystallized at 800 °C. The CSD ITO channel layer was annealed at 600 °C in a N 2 or O 2 atmosphere.…”
Section: Electrical Properties Of Metal-ferroelectric-semiconductor S...mentioning
confidence: 99%
“…16−18 The sputtering technique is an effective method for preparing HZO due to its low cost and flexible deposition conditions. 19 It was found that the best doping concentration of ferroelectric properties in the Hf X Zr 1−X O 2 system is X = 0.5. 20 In recent years, based on HfO 2 -based ferroelectric thin films, negative capacitance field-effect transistors (NCFETs) with different channels such as Si, Ge, WSe 2 , and MoS 2 have been investigated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…HZO thin films have been widely studied in the past. , Most of the reported HZO films were deposited by atomic layer deposition (ALD). However, carbon contaminants are unavoidable in HZO films during the ALD process, which have a negative effect on the formation of the o-phase. The sputtering technique is an effective method for preparing HZO due to its low cost and flexible deposition conditions . It was found that the best doping concentration of ferroelectric properties in the Hf X Zr 1– X O 2 system is X = 0.5 …”
Section: Introductionmentioning
confidence: 99%